Androgen replacement therapy in women. Issue 5 (September 2012) - Lebbe, Marie; Hughes, David; Reisch, Nicole; Arlt, Wiebke
Female androgens are derived from either the adrenal and peripheral conversion of the adrenal sex steroid precursor, dehydroepiandrosterone, or from direct ovarian production. Adrenal insufficiency or bilateral oophorectomy (surgical menopause) result in severe androgen deficiency, which can be clinically associated with impaired libido, drive and energy. Physiological menopause does not necessarily lead to androgen deficiency. The previously suggested definition of female androgen deficiency syndrome, as the concurrent presence of low androgen levels and low libido, is not precise enough and may lead to overdiagnosis. Current replacement options include transdermal testosterone or oral dehydroepiandrosterone treatment, both of which have been shown to result in significant improvements, in particular in libido and mood, while long-term effects on body composition, cardiovascular and cancer risk are less documented. Owing to these concerns, androgen replacement should be reserved for women with severe androgen deficiency due to an established cause and matching clinical symptoms.